From the Greek Revolution of 1821 to the Metapolitefsi: Historiographical Debates in Greece across Two Centuries - Karamanolakis, Vangelis; Triantafyllou, Christos (Historein, 2021)
Nowadays, with the celebration of the Greek state’s bicentennial, the exploration of how the national past was debated, historicised and narrated through historiographical and political means holds an interesting position: by examining how certain pasts entered the national canon, how events and figures were pantheonised, and how history and memory wars were conducted, we may be able to assess why and how nation-states commemorate themselves and formulate narratives about the shared past. Using the past as a symbolic resource, the agents of political and social power seek to provide the definitive version of how and why did we arrive at the present. Simultaneously, these official versions of the past are constantly contested by opposing social forces, which frequently manage to have their versions merge with, incorporated into or stand alongside those of their opponents. It is through these procedures, namely historiographical debates such as these explored in this issue of Historein, that the past turns into history.